Association Between Fat Graft Retention and Blood Flow in Localized Scleroderma Patients: A Pilot Study - Wang, Hayson Chenyu; Li, Yunzhu; Li, Zhujun; Wang, Liquan; Li, Ziming; Long, Xiao (Frontiers in Medicine, 2022)
Background: Microcirculation plays a vital role in scleroderma physiopathology and the mechanism of fat survival. Objective: This study aims to assess the blood perfusion change after fat grafting and evaluate the relationship between blood perfusion and fat graft retention in patients with localized scleroderma (LS). Methods: A pilot study was conducted in LS patients receiving autologous fat grafting (AFG). Fat graft retention measured by magnetic resonance imaging (MRI) analysis and blood flow perfusion measured by laser speckle contrast imaging six months postoperatively was noted. PUMC Localized Scleroderma Facial Aesthetic Index was used to assess the improvement of facial aesthetic impairment. Results: The fat retention at the six-month follow-up was 34.56±11.89 percent. At the sixth month of follow-up, the relative blood perfusion at the lesion area was 115.08±14.39 PU, significantly higher than 100.42±10.62 PU at the pre-operation (p=0.010). The blood perfusion at follow-up increased by an average of 1.15±0.14 times before the operation. No association between the increase in the blood flow perfusions and fat graft retention was found (r=-0.082, p=0.811). Conclusion: Local blood perfusion in the lesion area relatively increased after AFG. But no direct relationship was found between fat retention and increased blood supply.